The composition and stability of the vaginal microbiome of healthy women - Samar Megbal Alhabardi; Sherif Edris; Ahmed Bahieldin; Rashad Rizk Al-Hindi (Journal of the Pakistan Medical Association, 2021)
Published in August- 2021